INDIVIDUAL PROFILE OF FUNCTIONAL HEMISPHERIC ASYMMETRY AND QUALITY OF LIFE IN PATIENTS WITH PARKINSON'S DISEASE - M. A. Bykanova; A. J. Kovalchuk; N. V. Pizova; D. S. Druzhinin (Klinicist)
Objective — to identify the relationship between the individual profile of functional hemispheric asymmetry (IPFA) and lateralization of the Parkinson's disease (PD) debut, as well as assess of their impact on anxiety and depressive disorders and quality of life of patients.Materials and methods. 70 patients with PD (28 men and 42 women, average age 63,1 ± 8,1 years) with disease duration 48 [36, 72] months (Me [25 %; 75 %]) were included. We used Hoehn and Yahr, UPDRS, EuroQol, PDQ-39 scales, scale of anxiety and Spielberger–Hanin Hamilton Depression. IPFA was determined using the protocol survey of 48 jobs during the period of inclusion of patients in the study.Results. In patients with right-sided IPFA right-sided debut of PD was more common (p < 0.05) and in patients with mixed IPFA — leftsided(p < 0.05) PD debut. There were no significant differences in levels of reactive, personal anxiety and depression at different IPFA dependingon the side of PD debut (p > 0.05) received. Quality of life scale PDQ-39 showed worse results in patients with right-in right IPFA debut in comparison with those in patients with left debut (p < 0.05). Quality of life by EuroQol-II scale was higher in patients with rightsided IPFA with the left debut of PD than in patients with right-debut (p < 0.05), and in patients with mixed IPFA with right debut compared to patients with left debut (p < 0.05).Conclusion. With the debut of PD in leading limb and preferential involvement of the dominant hemisphere poorer quality of life was observed. IPFA and clinical asymmetry did not affect on the level of anxiety and depressive disorders, which were revealed in more than twothirds of patients with PD.